1996
DOI: 10.2307/3054036
|View full text |Cite
|
Sign up to set email alerts
|

Differential Treatment of Corporate Defendants by Juries: An Examination of the “Deep-Pockets” Hypothesis

Abstract: Evidence that juries treat corporate defendants less favorably than individual defendants is often cited in support of the widely held view that juries are biased against wealthy “deep-pocket” defendants. Such evidence confounds defendant wealth and defendant identity. In two juror simulation experiments involving citizens on jury duty, these factors were separated by manipulating whether the defendant was described as a poor individual, a wealthy individual, or a corporation; the defendant's assets were descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 52 publications
3
51
1
Order By: Relevance
“…In theory, it should not matter whether the defendant is a small locally owned automobile repair shop or the Ford Motor Corporation. Jurors should 1 A number of studies have shown that corporate defendants pay greater compensation than individual defendants in both actual (Chin & Peterson, 1985)and simulated trials (Hans & Ermann, 1989;Wasserman & Robinson, 1980) although what might appear on the surface as a deep-pocket effect may actually be a defendant-identity effect (MacCoun, 1996). Wealthy defendants were not necessarily at a disadvantage.…”
Section: Proposals To Cap Punitive Damage Awardsmentioning
confidence: 99%
“…In theory, it should not matter whether the defendant is a small locally owned automobile repair shop or the Ford Motor Corporation. Jurors should 1 A number of studies have shown that corporate defendants pay greater compensation than individual defendants in both actual (Chin & Peterson, 1985)and simulated trials (Hans & Ermann, 1989;Wasserman & Robinson, 1980) although what might appear on the surface as a deep-pocket effect may actually be a defendant-identity effect (MacCoun, 1996). Wealthy defendants were not necessarily at a disadvantage.…”
Section: Proposals To Cap Punitive Damage Awardsmentioning
confidence: 99%
“…This theory postulates that people are inclined to demand greater compensation from those whom they believe are wealthier and more able to afford such compensations [74]. Second, the "defendant identity effect", where damage compensations are biased according to the identity of the sued party [75].…”
Section: Compensation Demanded and Its Relation With Perceived Risk mentioning
confidence: 99%
“…Damage awards differ when the defendant is a corporation rather than an individual, even when all other facts of the case are held constant (Hans & Ermann, 1989;MacCoun, 1996). Several theories have emerged to explain why jurors hold corporations to a different standard than they hold individuals.…”
Section: Corporate Versus Individual Defendantsmentioning
confidence: 99%
“…When findings indicated that corporate defendants were required to pay larger awards than individuals, experimenters cited such results as support for the deep pocket hypothesis. MacCoun (1996) noted that such experiments confound wealth with defendant's status as a corporation or individual. To eliminate this confound, the author designed an experiment with three defendant conditions: a wealthy corporation, a wealthy individual, and a poor individual.…”
Section: Corporate Versus Individual Defendantsmentioning
confidence: 99%
See 1 more Smart Citation